Role of Community in Disaster Managements - Dr. Vinod Kumar (Journal of Advanced Research in Education, 2023)
In the present scenario, our vulnerable population and communities have become increasingly vulnerable to disasters and this has been aggravated by the micro level issues of rapid environmental degradation, resource depletion and global warming/climate change as well as the macro-level issues of poverty, illiteracy and lack of safety nets, amongst others. Thus, when disasters strike a geographical location, they tend to disproportionately alter the social fabric leading to wide spread damage and losses of lives and resources. As the state counts up the human and economic losses, or administers relief, those who experience disasters are conceptualized as a homogenous group called ‘victims’, a category which overlooks differences in terms of gender, caste, class, age or physical and mental ability (Fordham, 1999). The disruptions, thus, defy all existing social differences and stratifications, affecting all and, in a unique way, unifying the communities across boundaries. Being the first to suffer, the affected community rises like a phoenix and also becomes first real time responder in any disaster situation ignoring the inherent differences and stratifications of the community. This ‘community spirit’ or the social capital is thus a crucial strength on which the community balances its existence in a disaster scenario. This research paper based on the Secondary data. In this research paper discuss need, components, case studies; issues and challenges in the Community-Based Disaster Management.